Small scale embedded generation (SSEG) in Cape Town: a case study on the impact of Cape Town's SSEG regulation - Oliver, Dominic (Department of Environmental and Geographical Science, 2022)
In recent years, the rapidly diminishing costs of renewable technologies have rendered solar photovoltaics (PV) price competitive at a range of scales. Globally, there has been an increasing proliferation of distributed renewable generation embedded within the electricity network, called Small-Scale Embedded Generation (SSEG). Yet, while such decentralised technologies have taken a central role in discussions on energy transitions in the Global North, their implications in the Global South remain poorly documented. In South Africa, the convergence of a legacy energy system, supply issues, rising electricity prices, and growing environmental awareness as well as rapid urbanisation and persistent poverty is presenting a set of compound challenges for government at all levels and threatens the transition to a sustainable, low-carbon energy system. This study investigates the implications of SSEG on Cape Town's energy transition and assesses the drivers and impacts of regulatory responses. The study adopts a multi-level perspective on sociotechnical transitions deployed at the municipal scale to explore the role of SSEG in a just and sustainable energy transition. This was done along three dimensions using an environmental justice framework proposed by Cock (2004), wherein a green agenda refers to environmental conservation, a brown agenda represents energy impacts on quality of life and development, and a red agenda represents social justice and equality. Achieving a just transition will require attention to each of the three agendas in this framework. Using data from a desktop analysis, policy review and ten semi-structured interviews to investigate the case of Cape Town, the study found that the impacts of SSEG are dependent on the contextual landscape within which this transition is situated. Regulation of SSEG is largely the result of municipal attempts to protect its financial ability to fulfil developmental mandates. Recent regulatory developments have resulted in several unintended consequences which have reduced the extent to which green energy is equitably distributed across the municipal grid, and failed to mitigate revenue impacts of SSEG, and consequently the ability of municipalities to continue developmental agendas. National landscape pressures from increasing electricity prices and continued load-shedding are driving SSEG uptake. In response to these pressures, and municipal regulation, SSEG has adapted to new niches and battery technologies have become increasingly prevalent. Left unregulated SSEG will continue to threaten the financial viability of municipalities and the extent to which the ongoing energy transition in South Africa will be just and equitable. This study contributes to an emerging social-science research agenda into socio-technical transitions and addresses the limited consideration of the implications of disruptive technologies and their regulation at the city regime scale in the Global South.